2008
DOI: 10.1097/inf.0b013e31815922c8
|View full text |Cite
|
Sign up to set email alerts
|

Viral Etiology of Acute Respiratory Infections With Cough in Infancy

Abstract: Rhinoviruses, coronaviruses, HMPV, and HBoV are common pathogens associated with respiratory symptoms in otherwise healthy infants. They should be considered in the differential diagnosis of the aetiology of ARI in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
87
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 26 publications
12
87
3
4
Order By: Relevance
“…This observation was confirmed in two birth cohort studies, both in 197 unselected infants [47] and in 263 infants with risk factors for atopic sensitisation [48]. JACKSON et al [49] evaluating 289 newborns at risk for atopy up to the age of 6 yrs, found that moderate-to-severe RV wheezing illness was the most significant risk factor not only for the development of preschool wheezing at the age of 3 yrs, but also for the development of asthma at the age of 6 yrs.…”
Section: From Bronchiolitis To Wheezing Bronchitissupporting
confidence: 63%
“…This observation was confirmed in two birth cohort studies, both in 197 unselected infants [47] and in 263 infants with risk factors for atopic sensitisation [48]. JACKSON et al [49] evaluating 289 newborns at risk for atopy up to the age of 6 yrs, found that moderate-to-severe RV wheezing illness was the most significant risk factor not only for the development of preschool wheezing at the age of 3 yrs, but also for the development of asthma at the age of 6 yrs.…”
Section: From Bronchiolitis To Wheezing Bronchitissupporting
confidence: 63%
“…Morbidity associated with viral pneumonia is particularly high in children [8]. Distinguishing viral from bacterial pneumonia is helpful in initiating appropriate care (using antiviral vs antibacterial agents) in a timely fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses are common pathogens associated with respiratory symptoms in children [7,8]. Morbidity associated with viral pneumonia is particularly high in children [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RVs are the most frequent pathogens detected during both upper and lower respiratory tract infections and are associated with a large spectrum of clinical outcomes in this age group [4,5]. In the very young, they are one of the leading agents of bronchiolitis, second only to respiratory syncytial virus (RSV), and in children aged .12 months of age they are predominant pathogens associated with wheezing episodes [6][7][8].…”
mentioning
confidence: 99%